A 2:1 atrioventricular block presenting paradoxical ventriculophasic response. Issue 4 (19th March 2019) - Nakashima, Takashi; Suzuki, Keita; Ido, Takahisa; Yamaura, Makoto; Takahashi, Shigekiyo; Aoyama, Takuma
Abstract: Ventriculophasic response (VR) is defined as the shortening of the sinus cycle length in the setting of greater than second‐degree atrioventricular (AV) block. Typically, the PP intervals interposing a QRS complex are shorter than those without a QRS complex. Paradoxical VR is a rare clinical entity. We report about an 80‐year‐old man presenting with a 2:1 AV block, in whom typical and paradoxical VRs were observed.